Chemical Composition and In Vitro Dry Matter Digestibility of Some Important Grasses - Gupta, P C; Singh, Randhir; Singh, Kripal; Pradhan, K (Annals of Arid Zone, 2016)
Eighteen important grasses were analysed for chemical composition and in vitro dry matter digestibily. The per cent dry matter content ranged from 22.35 to 35.50, CP from 2.62 to 17.50, NDF from 53.60 to 74.00, cell content from 26.00 to 46.40, ADF from 28.05 to 4.60, hemicellulose from 24.31 to 36.60, lignin from 2.30 to 6.80, cellulose from 19.45 to 36.00, silica from 1.80 to 4.30 and in vitro dry matter digestibility from 55.56 to 69.44. In general, the values for various cell wall constituents and in vitro dry matter digestibility were well comparable to tl10se reported earlier for cereal forages.